2013
DOI: 10.5796/electrochemistry.81.674
|View full text |Cite
|
Sign up to set email alerts
|

Raman and DFT Study of the Reaction of Hydrazine and Hypophosphite on a Cu Surface in the Electroless Deposition Process

Abstract: Oxidation of the reductants is a dominant factor in the electroless deposition process. In order to obtain fundamental knowledge about the reaction mechanism of reductant oxidation for more precise control of the solid-liquid interface in this process, we have attempted to characterize the behavior of reductants adsorbed on Cu surface by using plasmon antenna enhanced Raman scattering. The concentric-patterned antenna coated with Cu, which consisted of a dimple array with single hole or a single hole with coax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The application of electroless Co film to magnetic recording media was first proposed by Electroless NiP film [110] [111,112]. Moreover, they studied the behavior of reductants adsorbed to the Cu surface by plasmon antenna enhanced Raman scattering and modeled this effect by Density Functional Theory (DFT) calculation [113].…”
Section: Electroless Plating For Micro Magneticsmentioning
confidence: 99%
“…The application of electroless Co film to magnetic recording media was first proposed by Electroless NiP film [110] [111,112]. Moreover, they studied the behavior of reductants adsorbed to the Cu surface by plasmon antenna enhanced Raman scattering and modeled this effect by Density Functional Theory (DFT) calculation [113].…”
Section: Electroless Plating For Micro Magneticsmentioning
confidence: 99%
“…490 Although Cu is prone to oxidation and exhibits a weaker SERS response than Au, it also readily chemisorbs a variety of organic analytes that favors its use for repetitive routine analyses. 491 The conformal nature of EL deposition is ideally suited for the fabrication of effective S E R S s u b s t r a t e s u s i n g n a n o s t r u c t u r e d t e mplates, 91,482,483,492,493 which require the deposition of reproducible, uniform metal surfaces to replicate the template structure.…”
Section: ■ Elementsmentioning
confidence: 99%
“…Experimental evidence indicates that the H • (ads) species can react to form H 2 via eq , which is released from the surface, or reduce Ni II to Ni I via eq , which disproportionates to deposit additional Ni 0 metal per eq : In closing this section, we note the extensive DFT molecular modeling and experimental work concerning H 2 PO 2 – oxidation spanning more than two decades to date by the Homma group. , These researchers have utilized DFT modeling, in conjunction with plasmon-enhanced Raman measurements, to better understand and observe H 2 PO 2 – intermediates present during the oxidation reaction. Their efforts have demonstrated that oxidation requires the formation of 5-coordinate, rather than 3-coordinate, intermediates.…”
Section: Elementsmentioning
confidence: 99%
“…We also attempted to develop an approach to combine in situ surface-enhanced Raman spectroscopy with theoretical calculations for analyzing the behavior of reductants and additives in detail, [25][26][27] and these approaches will provide possibilities to achieve further precise control of deposition.…”
Section: Theoretical Analysis On the Reaction Mechanism Ofmentioning
confidence: 99%